(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Big Data has the potential to bring valued insights for advanced decision making. It has become a trending practice to adopt Big Data into their process. It has attracted both the academicians as well as the industry people. A voluminous amount of diverse data is generated every day, and Big Data has emerged as an approach to process them. Data can be analysed in a different manner depending upon the requirement. The paper identifies the challenges and issues associated with Big Data and points out the research and industry opportunities in this field.